Enhancing the performance of Transmission Lines by FACTS Devices using GSA and BFOA Algorithms - Karuppiah, N.; Muthubalaji, S.; Ravivarman, S.; Asif, Md.; Mandal, Abhishek (International Journal of Engineering and Technology, 2018)
Flexible Alternating Current Transmission System devices have numerous applications in electrical transmission lines like improvement of voltage stability, reactive power compensation, congestion management, Available Transfer Capacity enhancement, real power loss reduction, voltage profile improvement and much more. The effectiveness of these FACTS devices is enhanced by the placement of these devices in the transmission lines. The placement is based on transmission line sensitivity factors such as Bus voltage stability index and line voltage stability index. This research article focuses on optimizing the location, number and ratings of FACTS devices using Evolutionary Algorithms like Bacterial Foraging Algorithm and Gravitational search algorithm. FACTS devices such as Static Var Compensator, Thyristor Controlled Series Capacitor and Unified Power Flow Controller are placed on IEEE 14 bus and IEEE 30 bus systems for reducing the real power loss in the transmission system. The results show that the performance of the transmission lines is enhanced more using Bacterial Foraging Algorithm than Gravitational Search Algorithm.Â Â